Implications of Ellipsis Cohesion in Al-Furuq Book Zainal Abidin Munawwir's Work and Its Translation into Indonesian - Ummi Rohmatuningsih; Arief Ma'nawi; Sajarwa Sajarwa (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Elliptical cohesion is a part of research in the field of translation science, namely the expression of meaning from one language to another language as intended by the author. This study aims to identify the types of ellipsis cohesion found in Kitab Al-Furuq by KH. Zainal Abidin Munawwir and its Indonesian translation. It also seeks to analyze the translation strategies employed by the translator in handling ellipsis. Kitab Al-Furuq, which translates to ‘several differences’ in Indonesian, is one of the works of KH. Zainal Abidin Munawwir from the Al-Munawwir Islamic boarding school in Krapyak, Yogyakarta. It consists of 39 chapters across 60 pages, discussing differences in several Islamic jurisprudence (fiqh) rulings related to worship practices. This study employs a qualitative descriptive method, using translational, comparative, and interpretative approaches. The analysis identified 54 instances of ellipsis cohesion, consisting of 27 nominal ellipses, 8 verbal ellipses, and 19 clausal ellipses. Ellipsis in the source language, Arabic, when translated into the target language, Indonesian, results in different types, forms, and meanings. This variation occurs due to the distinct linguistic characteristics of Arabic and Indonesian. These ellipsis findings contribute to making both the source and target texts more concise, dense, and efficient while avoiding word repetition.